The Association of an Early Net Ultrafiltration Rate and 28-Day Mortality in Patients Receiving Continuous Kidney Replacement Therapy - Wu, Buyun; Shen, Yining; Peng, Yudie; Xing, Changying; Mao, Huijuan (Frontiers in Medicine, 2021)
Background: An early net ultrafiltration (NUF) rate may be associated with prognosis in patients receiving continuous kidney replacement therapy (CKRT). In this study, we tested whether high or low early NUF rates in patients treated with CKRT were associated with increased mortality. Methods: We conducted a retrospective, observational study among all patients in the Medical Information Mart for Intensive Care IV database who received CKRT for more than 24 hours within 14 days after intensive care unit admission. We defined the early (initial 48 hours) NUF rate as the amount of fluid removal per hour adjusted by the patients’ weight and took it as a classified variable (low rate: < 1.6, moderate rate: 1.6–3.1 and high rate: > 3.1 mL/kg/h). The association between 28-day mortality and the NUF rate was analyzed by logistic regression and mediation analyses. Results: A total of 911 patients were included in our study. The median NUF rate was 2.71 (interquartile range 1.90–3.86) mL/kg/h and the 28-day mortality was 40.1%. Compared with the moderate NUF rate, the low NUF rate (adjusted odds ratio 1.56, 95% CI 1.04–2.35, p = 0.032) and high NUF rate (adjusted odds ratio 1.43, 95% CI 1.02–2.01, p = 0.040) were associated with higher 28-day mortality. The putative effect of high or low NUF rates on 28 day mortality was not direct [adjusted average direct effects (ADE) for a low NUF rate = 0.92, p = 0.064; adjusted ADE for a high NUF rate = 1.03, p = 0.096], but mediated by effects of the NUF rate on fluid balance during the same period [adjusted average causal mediation effects (ACME) 0.96, p = 0.010 for a low NUF rate; adjusted ACME 0.99, p = 0.042 for a high NUF rate]. Moreover, we found an increase trend in the NUF rate corresponding to the lowest mortality when fluid input increased. Conclusion: Compared with NUF rates between 1.6–3.1 mL/kg/h in the first 48 hours of CKRT, NUF rates > 3.1 mL/kg/h and < 1.6 mL/kg/h were associated with higher mortality.